Base-catalyzed monofunctionalization of N-alkyl activated azaarenes to construct 2-Iminoderivatives. (26th January 2023) - Duan, Dehao; Cai, Fangyuan; Wu, Yi; Gong, Quan; Huang, Aiqiong; Yi, Dongcheng; Li, Yinbao; Lai, Yingzhen; Peng, Xiang-Jun
Abstract: An efficient and simple synthesis of various N -sulfonylimino quinolines and pyridines had been achieved via monofunctionalization of quinoliniums and pyridiniums, which could regioselectively favor in nucleophilic attack at the C-2 position. This base-promoted methodology has been directly to form the 2-sulfonylimino derivatives with simple available starting materials, metal-free conditions, and high regioselectivity. Graphical abstract: We have successfully discovered a base-catalyzed one-pot amidation of quinoliniums, pyridiniums and sulfonyl azides, which enabled the synthesis of a wide range of 2-imino-quinolines and pyridines with excellent synthetic efficiency in metal-free systems. Image 1